Synthesis and biological evaluation of 7-methoxy-1-(3, 4, 5-trimethoxyphenyl)-4, 5-dihydro-2H-benzo[e]indazoles as new colchicine site inhibitors. Issue 18 (15th September 2019) - Jiang, Junhang; Zhang, Qingsen; Guo, Jiapeng; Fang, Shaoyu; Zhou, Ruolan; Zhu, Ju; Chen, Xin; Zhou, Youjun; Zheng, Canhui
Graphical abstract: Highlights: New colchicine site inhibitors with locked bioactive configuration were found. Compounds C1 and C2 showed potent inhibitory activity against tubulin polymerization. C1 and C2 showed potent inhibitory activity against human colon cancer cell lines. Compound C1 showed excellent broad-spectrum antitumor activity in the NCI-60 Screen. Abstract: The colchicine site inhibitors (CSIs) displayed both antimitotic and vascular disrupting activities, therefore are promising potential antitumor agents. In this study, a series 1-phenyl-4, 5-dihydro-2 H -benzo[ e ]indazoles were found as new CSIs of which the bioactive configuration was locked. Among them, compounds C1 and C2 displayed the best activity, with tubulin polymerization IC50 of 3.4 and 1.5 μM, and growth IC50 of low nanomolar concentrations against human colon cancer cell lines. In addition, compound C1 showed excellent broad-spectrum antitumor activity in the NCI-60 Human Tumor Cell Lines Screen, encouraging further study of this antitumor compound.